The Effect of Game – Like Exercisers According to Click Scout On Some Skill Performance Types In Volleyball Primer League Players - Abed al mutalib, Jaffer; Ali, Tariq (Journal of Physical Education, 2019)
The research aimed at designing game – like exercises according to clicks and scout on some skill performance types in volleyball primer league players as well as identifying the effect of these exercises on some skill performance types in volleyball primer league players. the researchers used the experimental method on (8) volleyball clubs 2018 – 2019 yet the subjects were (14) players from Al Senaa club. The researchers applied click and scout analytical program then the data was collected and treated using proper statistical operations to conclude that the experimental group surpassed in post analyses of some skill performance types and it was effective as well. The researchers finally recommended the necessity of using the proposed exercises in volleyball primer league to develop skill performance level as well as making similar studies on other variables and subjects.